2019
DOI: 10.1111/apt.15381
|View full text |Cite
|
Sign up to set email alerts
|

Formation of semi‐enveloped particles as a unique feature of a hepatitis B virus PreS1 deletion mutant

Abstract: Summary Background Naturally occurring variants with deletions or mutations in the C‐terminal PreS1 domain from hepatitis B virus (HBV) chronically infected patients have been shown to promote HBsAg retention, inhibit HBsAg secretion and change the extracellular appearance of PreS1‐containing HBV particles (filaments and virions). Aims To study the impact of N‐terminal deletion in preS1 domain on viral secretion and morphogenesis. Methods An HBV mutant with 15 amino acids (aa 25‐39) deletion in N‐terminal preS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
(190 reference statements)
0
15
0
Order By: Relevance
“…Based on a variant isolated from a patient suffering from chronic HBV that lacks aa 25-39 in the N-terminus of PreS1, it was found that the N-terminal PreS1 domain determines LHBs secretion and triggers proper assembly of HBV virions. This deletion caused a significant fraction of semi-enveloped viral particles, a variant that has not been described before [108]. The discrepancy between these studies could be based on the different experimental strategies.…”
Section: Envelopmentmentioning
confidence: 87%
See 2 more Smart Citations
“…Based on a variant isolated from a patient suffering from chronic HBV that lacks aa 25-39 in the N-terminus of PreS1, it was found that the N-terminal PreS1 domain determines LHBs secretion and triggers proper assembly of HBV virions. This deletion caused a significant fraction of semi-enveloped viral particles, a variant that has not been described before [108]. The discrepancy between these studies could be based on the different experimental strategies.…”
Section: Envelopmentmentioning
confidence: 87%
“…The discrepancy between these studies could be based on the different experimental strategies. In the study from Jiang et al [108], HBV particle gel essay, HBV mixed ELISA and electron microscopy were mainly used to discriminate partially-enveloped viral particles from fully assembled viral particles. The above mentioned study by Bruss et al [106] performed immuno-precipitation and subsequent radioactive endogenous polymerase reaction (EPR) to quantify HBV viral particles, which fails to distinguish between partially-enveloped virions and intact enveloped virions.…”
Section: Envelopmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors' declarations of personal and financial interests are unchanged from those in the original article …”
Section: Acknowledgementsmentioning
confidence: 99%
“…In a recent issue of AP&T, Jiang et al described the characterisation of an envelope deletion variant of hepatitis B virus (HBV) isolated from a patient. The authors showed that the deleted amino acid domain 25‐39 of PreS1 contributes to viral morphogenesis and affects hepatitis B surface antigen (HBsAg) secretion.…”
mentioning
confidence: 99%